L’alcalde de barrio en Espagne au XVIIIe siècle : diffusion territoriale et adaptations locales - Brigitte Marin (Centre de Recherches sur les Mondes Américains, 2017)
In 1766 the motín d’Esquilache led to the restructuring of the Madrid police. The creation of sixty-four alcades de barrio to strengthen the surveillance system was the most significant innovation. Starting in courtrooms and chancery centres, these new types of police and justice deputies quickly spread throughout Spanish towns from 1769 onwards. This article examines the profile of neighbourhood police forces in other European and Iberian towns in order to contextualise the measures adopted in Madrid in 1768 with similar older experiences often based on elective procedures still in place in the 18th century. Secondly, it looks at the actual implementation of the function of alcades de barrio in Spain in order to clarify some of the circumstances that might have facilitated their introduction and that might have progressively transformed their civic and honorary duty into a more professional one. The 1768 Madrid directives provided a unifying reference framework for practices in urban neighbourhood management and social control that were previously more fragmented.